The New Agriculture: From Food Farms to Solar Farms - Owley, Jessica; Morris, Amy Wilson (Columbia Journal of Environmental Law, 2019)
Across the United States, government agencies and energy developers are looking to agricultural land for development of renewable energy. One attraction of agricultural lands is that they are already relatively ecologically impaired compared with the previous solar development sites in the California and Arizona desert that have been a major source of concern for many environmental groups—and subject to expensive mitigation requirements under the Endangered Species Act. Renewable energy development pressures are accelerating the existing loss of agricultural land, heightening concerns about food security and the economic viability of agricultural communities. California farmland is at the center of this conflict. Suburban sprawl in California already leads to conversion of nearly 40,000 acres of agricultural land a year. Now, a new competitor has entered the scene: solar energy facilities. Both users compete for water, which is only becoming scarcer in the face of climate change and periodic drought. The pressures on California’s agricultural land have long inspired the state legislature and local governments to enact various measures to protect farmland and promote the business of agriculture. We examine the ways California’s Williamson Act (which provides tax benefits for agricultural land) and the California Environmental Quality Act (the state’s environmental review statute) have proven and not proven to be obstacles to taking agricultural land out of crop production and putting it into solar energy production. We demonstrate that current laws are neither protecting prime agricultural lands nor adequately creating conditions for evaluating the tradeoffs and alternatives when farmland—or ecologically sensitive habitat—is used for large-scale renewable energy development.